HUBUNGAN ANTARA CARA BELAJAR MAHASISWA AKTIF DAN MOTIVASI BELAJAR DENGAN PRESTASI BELAJAR MAHASISWA SEMESTER IV PADA MATA KULIAH ASUHAN KEBIDANAN I DI STIKES MITRA ADIGUNA PALEMBANG TAHUN 2011 - Tiara Fatrin (STIKES Abdurrahman. Pusat Informasi dan Manajemen, 2012)
Education is a conscious and well-planned effort to create an atmosphere of learning and learning process so that learners actively develop their potential to have spiritual spiritual power, self-control, personality, intelligence, noble character, as well as the skills needed of him and society. Learning achievement is the main benchmark to know the success of one's learning. One of the factors from within the students that determine the success or failure of students in the learning process is the way of active student learning and learning motivation. The purpose of this research is to know the relationship between the way of active student learning and learning motivation with student achievement of fourth semester of obstetric care subject I (pregnancy). This research is an analytical survey with Cross Sectional approach. The population in this study is all students of the fourth semester who have followed the course of Midwifery Care I (Pregnancy) In Midwifery Department Stikes Mitra Adiguna Palembang. The sample of this study was taken by random sampling and obtained the number of samples of 50 respondents. The result of univariate analysis showed good student achievement that is equal to 43 respondents (86,0%) and students who have enough learning achievement of 7 respondents (14,0%), active student learning method that is equal to 43 respondents (86,0% ) and the learning method of inactive students were 7 respondents (14.0%), high student learning motivation which was 38 respondents (76%) and low student learning motivation 12 respondents (24%). Based on bivariate analysis by using chi-square statistic test showed that there is a correlation between the way of active student learning with learning achievement (P. Value = 0,000) and no relationship between learning motivation and learning achievement (P.Value = 1,000).